Erasmus Guillain-Barre Syndrome Outcome Score (EGOS) to predict functional outcomes - Maria Ulfa; Titis Widowati; Agung Triono (Paediatrica Indonesiana, 2022)
Background Guillain-Barre syndrome (GBS) has a highly diverse clinical course and prognosis. Predicting functional outcomes is needed in order to give appropriate treatment and counseling. Erasmus Guillaine-Barre Syndrome Outcome Score (EGOS) is simple scoring based on age onset, pre existing diarhea and GDS score obtained from medical record and physical findings that can be used by clinician to predict the functional outcomes of the child with GBS.. Objective To assess the usefulness of EGOS to predict functional outcomes of GBS patients. Methods A retrospective cohort study to see the functional outcomes which is walking or not walking of children with GBS aged 6 months to 18 years hospitalized in RSUP Dr. Sardjito, Yogyakarta from 2014 to 2019 were enrolled by a purposive sampling method. Bivariate and logistic regression multivariate backward method analyses were used to assess for possible correlations between predictive factors and functional outcomes in GBS patients. Results A total of 33 patients were enrolled and analyzed. After six months of weakness, 57.1% of patients with high EGOS (> 4) had poor functional outcomes according to the Hughes scale, scoring to asses functional outcomes . Patient with high EGOS (> 4) had greater risk of poor functional outcomes compared to patients with lower EGOS (â‰¤ 4) (P=0.006; OR 33.3; 95%CI 2.74 to 404.94). Poor functional outcomes of GBS patients was not influenced by preceding upper respiratory tract infection, cranial nerve involvement, use of ventilator, autonomic dysfunction, immunotherapy, complicating disease, rehabilitation, or nutritional status. Conclusion High EGOS of >4 is a predictor for poor functional outcomes in children with GBS.